Legal Certainty of Inheritance for Children Born Out of Wedlock Who Are Recognized as Legitimate by Their Biological Parents - Putri, Quine Khadra Merdeka (Sultan Agung Notary Law Review, 2024)
The birth of a child out of wedlock has a large and broad impact, namely whether or not to receive an inheritance, therefore it must receive legal protection in order to obtain clarity regarding the position and distribution of the inheritance. The purpose of this study is to analyze: 1). The legal status of obtaining inheritance rights for illegitimate children who receive legal recognition from their biological parents. 2). Legal protection for obtaining inheritance rights for illegitimate children who receive legal recognition from their biological parents. The approach method used in this study is normative juridical and supported by empirical juridical. The research specification used is descriptive analytical. The type of data uses primary data obtained through literature studies. The data analysis method used in this study is descriptive analysis. The results of the study concluded: 1). The Legal Status of an Illegitimate Child who receives legal recognition from his biological parents to obtain inheritance rights is to continue to receive the right to inherit, an illegitimate child who is recognized is entitled to a will grant as long as the grant does not harm other heirs and is in accordance with the provisions stipulated by the Law. Wirjono Prodjodikoro said that if an illegitimate child wants to receive legal recognition from his biological father, it must be based on the recognition and determination of the court. After receiving recognition and determination from the court, the illegitimate child has a civil relationship with his biological father and becomes an erfgenaam or legal heir according to law and statute and is entitled to receive inheritance from his biological father. 2). Legal Protection for Illegitimate Children who receive recognition from their biological parents to obtain inheritance rights is after the Constitutional Court (MK) Decision Number 46/PUU-VIII/2010, the heir has the right to file a lawsuit to the court to obtain his inheritance, of course it must be accompanied by concrete evidence that confirms having a blood relationship with the deceased testator. For example, a DNA test letter from a Forensic Doctor and a court decision that confirms the DNA test letter.